A passive mitigation strategy of impurity deposition on the first mirrors using duct with baffles: A case study at a port of KSTAR with in-situ deposition monitoring - Kim, Boseong; Seon, Changrae; Oh, Soo Ghee; Kim, Yu Kwon; An, Younghwa; Bang, Eunnam; Hong, Suk Ho; Pak, Sunil; Cheon, Munseong; Lee, Hyun Gon (Fusion Engineering and Design, 2018)
We report our recent investigation on a passive mitigation strategy of the mirror deposition in magnetically confined fusion (MCF) devices, employing a newly designed duct system with baffles at KSTAR tokamak. Our mitigation strategy of the first mirror deposition is to suppress the deposition of impurity species onto the first mirror by confining inert gas such as helium in the duct with baffles located in front of the first mirror. To achieve this final goal, feasibility of this technique at a real tokamak was investigated with regard to the effect on the plasma condition in this paper. To assess the effect of the helium gas flow on the plasma condition, 5 sccm amount of helium gas was injected into the duct for about 70% of shots in the year 2016. This quantity of helium gas was found to be insignificant in terms of the effect on plasma performance. To estimate the deposition quantity on the sample during plasma operation in-situ, quartz crystal microbalances (QCMs) were also installed for thickness detection in real time at KSTAR. The net deposition rates of these samples at KSTAR were about 0.6–40 ng/h cm2 (2.7 × 10−3–0.18 nm/h (graphite)) depending on the kinds of operations such as plasma shots, glow discharge cleaning, and baking of the tokamak first wall. We found that the most detrimental condition with regard to the mirror deposition rate at KSTAR is the glow discharge wall cleaning (GDC) in the baking condition.
Keywords: Gas pressurization; Glow discharge cleaning; In-situ deposition; Mitigation strategy; Plasma conditions; Plasma operations; Plasma performance; Thickness detection; Deposition mitigation; Duct with baffles; Gas pressurization; Mirror deposition